A "luta por reconhecimento" no Facebook : a comunicação social nas redes sociais, uma interpretação sociológica - Souza, Mário César de (2016)
This dissertation text is inserted in an attempt to draw up an outline of a theme that is scoped to discuss the struggle for recognition on Facebook: social communication in social networks and its sociological interpretation. From this overall goal there is the intention to point out that with the rise of Facebook the struggle for recognition of the field was expanded. To reach such a conclusion, we analyze more specifically some forms of struggle for recognition that emerged within this social media as: personal, social and political; tipologizamos some actors who interact in this communicative space; cotejamos the online world with the offline world and point out that they are in imbrication stage. Last, but not least, we assess that, however that Facebook is considered a locus dominated by the freedom of expression of the subject, there are several factors that restrict the user's autonomy with regard to the struggle for recognition within this media social, as the normative expectations and moral character of claims with which they seek to provide ways to express their identities and their autorrealizações; the lack of operational content of Facebook instrument and, finally, the absence of control by the user over the fate of content flow it produces and exposes on Facebook.